Extensions 1→N→G→Q→1 with N=C2×3- 1+2 and Q=C2×C4

Direct product G=N×Q with N=C2×3- 1+2 and Q=C2×C4
C22×C4×3- 1+2144C2^2xC4xES-(3,1)432,402

Semidirect products G=N:Q with N=C2×3- 1+2 and Q=C2×C4
extensionφ:Q→Out NdρLabelID
(C2×3- 1+2)⋊1(C2×C4) = C2×C4×C9⋊C6φ: C2×C4/C4C2 ⊆ Out C2×3- 1+272(C2xES-(3,1)):1(C2xC4)432,353
(C2×3- 1+2)⋊2(C2×C4) = C22×C9⋊C12φ: C2×C4/C22C2 ⊆ Out C2×3- 1+2144(C2xES-(3,1)):2(C2xC4)432,378

Non-split extensions G=N.Q with N=C2×3- 1+2 and Q=C2×C4
extensionφ:Q→Out NdρLabelID
(C2×3- 1+2).1(C2×C4) = C8×C9⋊C6φ: C2×C4/C4C2 ⊆ Out C2×3- 1+2726(C2xES-(3,1)).1(C2xC4)432,120
(C2×3- 1+2).2(C2×C4) = C72⋊C6φ: C2×C4/C4C2 ⊆ Out C2×3- 1+2726(C2xES-(3,1)).2(C2xC4)432,121
(C2×3- 1+2).3(C2×C4) = Dic9⋊C12φ: C2×C4/C4C2 ⊆ Out C2×3- 1+2144(C2xES-(3,1)).3(C2xC4)432,145
(C2×3- 1+2).4(C2×C4) = D18⋊C12φ: C2×C4/C4C2 ⊆ Out C2×3- 1+272(C2xES-(3,1)).4(C2xC4)432,147
(C2×3- 1+2).5(C2×C4) = C2×C9⋊C24φ: C2×C4/C22C2 ⊆ Out C2×3- 1+2144(C2xES-(3,1)).5(C2xC4)432,142
(C2×3- 1+2).6(C2×C4) = C36.C12φ: C2×C4/C22C2 ⊆ Out C2×3- 1+2726(C2xES-(3,1)).6(C2xC4)432,143
(C2×3- 1+2).7(C2×C4) = C4×C9⋊C12φ: C2×C4/C22C2 ⊆ Out C2×3- 1+2144(C2xES-(3,1)).7(C2xC4)432,144
(C2×3- 1+2).8(C2×C4) = C36⋊C12φ: C2×C4/C22C2 ⊆ Out C2×3- 1+2144(C2xES-(3,1)).8(C2xC4)432,146
(C2×3- 1+2).9(C2×C4) = C62.27D6φ: C2×C4/C22C2 ⊆ Out C2×3- 1+272(C2xES-(3,1)).9(C2xC4)432,167
(C2×3- 1+2).10(C2×C4) = C42×3- 1+2φ: trivial image144(C2xES-(3,1)).10(C2xC4)432,202
(C2×3- 1+2).11(C2×C4) = C22⋊C4×3- 1+2φ: trivial image72(C2xES-(3,1)).11(C2xC4)432,205
(C2×3- 1+2).12(C2×C4) = C4⋊C4×3- 1+2φ: trivial image144(C2xES-(3,1)).12(C2xC4)432,208
(C2×3- 1+2).13(C2×C4) = C2×C8×3- 1+2φ: trivial image144(C2xES-(3,1)).13(C2xC4)432,211
(C2×3- 1+2).14(C2×C4) = M4(2)×3- 1+2φ: trivial image726(C2xES-(3,1)).14(C2xC4)432,214